Real options analysis in the engineering company practice - Václav Klepáč; Petr Kříž; David Hampel (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2013)
In this paper, we deal with the real options analysis of selected investment projects. This approach is supplemented and compared to calculations of the net present value (NPV). Two research problems are analyzed: acquisition of the simulation software for the foundry industry in the sense of the expansive options and options on leaving the project in the case of acquisition of the spectrometer. For the option valuation, there were used analytical and numerical methods like the Black-Scholes model, binomial model and Monte Carlo simulations. In the case of binomial pricing model we used modification describing the behavior of the project’s cash-flow (CF) due to capacity of the company, path-dependent addiction and embedded option barrier. To extend the application of the real options analysis, we propose procedures for sensitivity analysis and option pricing based on Monte Carlo simulations for particular case of stochastic volatility.